Description of Characteristics, Knowledge, and Behavior Towards the Hazards of Conventional Tobacco Cigarettes Among Cleaning Service and Security Workers Who Smoke - Situmorang, Daniel Reinaldo Parsaoran; Salutondok, Welly; Simarmata, Vidi Posdo A. (Jurnal KESANS : Kesehatan dan Sains, 2025)
Introduction: Conventional tobacco cigarette smoking remains a major public health concern, particularly among occupational groups exposed to high work-related stress, such as cleaning service and security workers. Limited awareness of smoking-related health risks may contribute to continued smoking behavior and increased disease burden. Objective: This study aimed to describe the characteristics, knowledge levels, and smoking behaviors related to the dangers of conventional tobacco cigarettes among cleaning service and security workers at the Faculty of Medicine, University X, Jakarta. Method: This descriptive cross-sectional study was conducted in July 2023 among cleaning service and security personnel who were active smokers. Data were collected using a structured questionnaire covering demographic characteristics, knowledge of smoking hazards, and smoking behaviors. Data were analyzed using descriptive statistics. Result and Discussion: The results showed that 62% (31 respondents) had good knowledge regarding the dangers of conventional tobacco cigarettes, while 38% (19 respondents) had sufficient knowledge, and none had poor knowledge. In terms of smoking behavior, 38% of respondents always smoked, 24% often smoked, 34% sometimes smoked, and 4% never smoked in certain situations. Despite relatively adequate knowledge, risky smoking behaviors remained common. Conclusion: Although respondents generally had adequate knowledge, risky smoking behaviors persisted, indicating the need for targeted health education and smoking cessation programs for this occupational group